ON THE FRACTIONAL DIRAC SYSTEMS WITH NON-SINGULAR OPERATORS - Ercan, Ahu (Vinca Inst Nuclear Sci, 2019)
In this manuscript, we consider the fractional Dirac system with exponential and Mittag-Leffler kernels in Riemann-Liouville and Caputo sense. We obtain the representations of the solutions for Dirac systems by means of Laplace transforms.
Keywords: Dirac operator; fractional; exponential kernel; Mittag-Leffler kernel; Laplace transform